Seeing God in Our Birth Experiences: A Psychoanalytic Inquiry into Pre and Perinatal Religious Development - Holmes, Helen (Routledge Studies in Religion Ser., 2020)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Dedication -- Acknowledgements -- Preface -- Introduction -- 1 Rizzuto and Freud: parental origins of images of God -- 2 Klein and Bion: the intrauterine in relation to images of God -- 3 The not knowing position in relation to prenatal and perinatal life -- 4 The perinatal origins of images of God -- 5 Epigenesis, attachment and God representations -- 6 The question of prenatal and perinatal underpinnings of God images -- 7 Prenatal religious affect -- Conclusions -- Bibliography -- Index.